Mammary differentiation induces expression of Tristetraprolin, a tumor suppressor AU-rich mRNA-binding protein - Goddio, M. Victoria (2012)
Tristetraprolin (TTP) is a RNA-binding protein that inhibits the expression of pro-inflammatory cytokines and invasiveness-associated genes. TTP levels are decreased in many different cancer types and it has been proposed that this protein could be used as a prognostic factor in breast cancer. Here, using publicly available DNA microarray datasets, “serial analysis of gene expression” libraries and qRT-PCR analysis, we determined that TTP mRNA is present in normal breast cells and its levels are significantly decreased in all breast cancer subtypes. In addition, by immunostaining, we found that TTP expression is higher in normal breast tissue and benign lesions than in infiltrating carcinomas. Among these, lower grade tumors showed increased TTP expression compared to higher grade cancers. Therefore, these data indicate that TTP protein levels would provide a better negative correlation with breast cancer invasiveness than TTP transcript levels. In mice, we found that TTP mRNA and protein expression is also diminished in mammary tumors. Interestingly, a strong positive association of TTP expression and mammary differentiation was identified in normal and tumor cells. In fact, TTP expression is highly increased during lactation, showing good correlation with various mammary differentiation factors. TTP expression was also induced in mammary HC11 cells treated with lactogenic hormones, mainly by prolactin, through Stat5A activation. The effect of this hormone was highly dependent on mammary differentiation status, as prolactin was unable to elicit a similar response in proliferating or neoplastic mammary cells. In summary, these studies show that TTP expression is strongly linked to the mammary differentiation program in human and mice, suggesting that this protein might play specific and relevant roles in the normal physiology of the gland.